Wort und Wirklichkeit: Überlegungen beim Lesen von Markus Gabriels Fiktionen - Poppenberg, Gerhard (Philosophische Rundschau, 2021)
The essay debates critically Markus Gabriel's study Fiktionen from the point of view of philology contrasting the philosophical theory of fiction delivered by Gabriel with the discussions of the same topic in literary theory on the one hand and with the discussions of premodern scholasticism about a possible ontology of the chimaera on the other hand in the context of medieval nominalism and realism. A philological interpretation of the tale The Aleph written by Jorge Luis Borges offers an alternative to the philosophical reading of Gabriel's and marks the point of difference between the philosophical and the philological reflections.